ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI REALISASI KREDIT MIKRO PADA BANK CIMB NIAGA UNIT SUBRANTAS - PETRUS HASUDUNGAN SITINJAK; RUZIKNA " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Bank as a financial institution that has a role as a financial intermediary, has 3 functions: gathers funds from the excess funds, disburse funds on behalf of a shortage of funds and provide services to other services. Bank as a financial institution can help the party with disburse funds shortage of credit. Granting credit must also be accompanied by the appropriate policies of the Government.Credit that would have been realized had passed the stage of credit analysis undertaken by the bank. As for credit analysis performed by the bank includes principle 5 c. credit must be realized to every customer affected by several factors such as: the value of guarantees, income, Loan history and working capital needs.This study uses secondary data analysis and use descriptive statistics. As for knowing how the realization of credit at the Bank CIMB Niaga Subrantas units as well as the factors that affected it, that is with the use of quantitative analysis by using multiple linear regression. Data processing using the computer program with software SPSS 15.These results indicate that the value of collateral, working capital requirements and income have a real influence on the amount of credits allocated. It is seen from each variable has a value rhitung > rtable, and a significance value of each variable is smaller than 0.05.Keywords: Bank, Credit, realization, analysis